2014
DOI: 10.1590/0004-2730000003174
|View full text |Cite
|
Sign up to set email alerts
|

Leptin replacement therapy for the treatment of non-HAART associated lipodystrophy syndromes: a meta-analysis into the effects of leptin on metabolic and hepatic endpoints

Abstract: RESUMOAs manifestações clínicas das síndromes lipodistróficas (SL) incluem hipoleptinemia, hiperglicemia, resistência insulínica, dislipidemia e esteatose hepática. A terapia de reposição de leptina (TRL) melhora tais parâmetros, mas atualmente não há dados compilados demonstrando tal efeito. Uma revisão sistemática dos bancos de dados MEDLINE e Cochrane Library identificou estudos avaliando os efeitos da TRL sobre parâmetros metabólicos e hepáticos em pacientes com SL não associadas ao uso de antirretrovirais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Since lipodystophy clearly indicates changes in adipose storage, the resultant altered adipokine levels may lead to the observed metabolic dysfunction in lipodystrophy. Lipodystrophy is characterized by hypoleptinemia and can be congenital or acquired, such as for HIV-associated lipodystrophy syndrome (HALS) or highly active antiretroviral therapy (HAART) [44,45,46*]. Indeed, lipoatrophy is a state of leptin deficiency [45,46*], and leptin replacement therapy improves insulin resistance and metabolic syndrome in animal models of lipoatrophy [47].…”
Section: Leptin Deficiencymentioning
confidence: 99%
“…Since lipodystophy clearly indicates changes in adipose storage, the resultant altered adipokine levels may lead to the observed metabolic dysfunction in lipodystrophy. Lipodystrophy is characterized by hypoleptinemia and can be congenital or acquired, such as for HIV-associated lipodystrophy syndrome (HALS) or highly active antiretroviral therapy (HAART) [44,45,46*]. Indeed, lipoatrophy is a state of leptin deficiency [45,46*], and leptin replacement therapy improves insulin resistance and metabolic syndrome in animal models of lipoatrophy [47].…”
Section: Leptin Deficiencymentioning
confidence: 99%
“…Further studies over the ensuing years continued to validate this initial response [2224]. A recent meta-analysis showed that metreleptin decreased fasting glucose (standardized mean difference [SMD] 0.75, range 0.36–1.13, P = 0.0001), HbA1c (SMD 0.49, range 0.17–0.81, P = 0.003), triglycerides (SMD 1.00, range 0.69–1.31, P < 0.00001), and liver volume (SMD 1.06, range 0.51–1.61, P = 0.0002) [25]. …”
Section: Leptin Replacement In Lipodystrophymentioning
confidence: 99%
“…Overall, this suggested that metreleptin was more effective in improving the condition of patients with the generalized form of lipodystrophy, even though there is also emerging evidence suggesting that the efficacy of metreleptin could be independent of lipodystrophy etiology. 15 , 16 , 29 Since patients with generalized lipodystrophy suffer more substantial mortality and morbidity due to complications arising from a number of severe metabolic abnormalities, 34 , 35 it is easier to ascertain and/or predict the beneficial outcome of metreleptin therapy in patients with generalized lipodystrophy, as opposed to patients with partial lipodystrophy. Furthermore, as patients with partial lipodystrophy showed a more heterogeneous disease profile, there was an increased variability in the severity of their metabolic abnormalities.…”
Section: Trials Of Metreleptin In Lsmentioning
confidence: 99%
“…In mice and in humans, leptin improves abnormalities of glucose and lipid metabolism, increases insulin sensitivity, reduces the risk of further progression into NAFLD, and restores gonadotropin secretion. 14 , 15 Due to some risks related to the development of neutralizing antibodies and lymphoma, US prescribers must be certified by enrolling in and completing specific training. Although it has been shown that LRT can be safe and effective also in patients with partial forms of lipodystrophy, 15 , 16 its use is currently approved only for cases of generalized non-HIV lipodystrophy.…”
Section: Introductionmentioning
confidence: 99%